Tinjauan Faktor-Faktor yang Mempengaruhi Karakteristik Tukang Terhadap Prestasi Kerja (Studi Kasus Proyek Area Kota Palu) - A. Asnudin; J. Josua (Civil Engineering Department, Tadulako University, 2023)
Human resources are one of the most important factors in determining the success of a project. Measurement of human resources is expressed in numerical values measured by workers based on influencing variables. The purpose of this study was to determine what factors influence the characteristics of workers on the work performance of a construction project. The method used in this study is a quantitative descriptive method by distributing questionnaires directly with the contents in accordance with the expected research, then the questionnaires are distributed in the field (Fence Rehabilitation Work at the Central Sulawesi BPS Office and Building Construction Work for the Meteorology, Climatology, and Geophysics Office Classroom). I) with a total o f 30 respondents. After obtaining data from the field with the help of questionnaires, then data processing is carried out which includes reliability tests, descriptive analysis, and Relative Rank Index (RRI) analysis. The results of the study indicate that the main factors that greatly affect the work performance of construction workers in the implementation of construction projects in Palu are the discipline factor with a 50% value presentation, the motivation factor with a 30% presentation and 20% productivity.